The role of African christian discourse in redefining identity, literature and language education in Southern Africa: the case of the founding text of Paul Mwazha’s African Apostolic church - Manyawu, Andrew T. (LWATI, 2016)
Being both a subject and a medium of learning, language is the vehicle through which society passes its worldview to youths. This raises questions of selection and grading of material to be incorporated into syllabi and textbooks. This paper argues that Southern African language syllabi need a paradigm shift in order to better reflect an African society seeking to reaffirm its identity after decades of oppression. There is need to open up the language curriculum to discourses widely consumed by Africans but hitherto ignored by formal educational systems still biased towards Western worldview. These include the discursive production of African Instituted Churches (AIC). The founding text of the African Apostolic Church (AAC) of Zimbabwean, Paul Mwazha, is examined from the perspective of intertextuality in order to illustrate its literary and educational value. A case is then made for the inclusion of such texts in secondary school curricula in Southern Africa.